HUBUNGAN PENGETAHUAN GIZI DENGAN PEMILIHAN MENU MAHASISWI UNIVERSITAS SARJANAWIYATA TAMANSISWA DI ASRAMA ASMADEWA YOGYAKARTA - Laily Miftahul Jannah (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
This study aimed to describe (1) the nutrient knowledge, (2) the choice of menu, and (3) correlation between nutrient knowledge with the choice of menu among the students of Sarjanawiyata Tamansiswa University in Asmadewa Hostel of Yogyakarta. This study was ex-post facto. Data colleting methods used questionnaires and documentation. Data analyzing methods used descriptive analysis and hypothesis testing by using Product Moment that was started by normality and linearity test.Â This study shows that the nutrient knowledge was in high category with the relative frequency 70.5% and the choice of menu was in high category with relative frequency 70.49%. Based on the result of Product Moment, the score of rxy was 0,642. The score of r table in the significant level 5% for total respondents 135 was 0.254 (rxy 0,642 > r table 0,254). It could be stated there was a positive and significant correlation between nutrient knowledge with the choice of menu. Â Key words: nutrient knowledge, choice of menu